1989
DOI: 10.2136/sssaj1989.03615995005300060013x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Reactivity of Soil Organic Matter Fractions in No‐Tilled and Tilled Cotton

Abstract: Because of the increased use of herbicides in no‐tilled soils and the difference in organic C distribution between tilled and no‐tilled soils, it is important to compare herbicide activity in different tillage systems. Soil humus fractions and characteristics were determined on surface Lexington silt loam soil (fine, silty, mixed, thermic Typic Paleudalf) samples of no‐tilled and tilled cotton field plots in West Tennessee. Soil humic and fulvic acid were extracted by standard methods. Total C ranged from 9.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…However, to our current knowledge, little work has been published on the effects of these changes in soil organic matter composition due to tillage on pesticide sorption. Ding et al (2002b) highlighted a stronger sorption of metolachlor by humin than by humic acids, and humin content was found to be higher under notillage systems (Stearman et al, 1989). For humin, which is a highly condensed form of soil organic matter, several studies showed that sorption was more variable and that sorption isotherms were less linear (Xing and Pignatello, 1997;Yuan and Xing, 1999).…”
Section: Organic Carbon Content Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our current knowledge, little work has been published on the effects of these changes in soil organic matter composition due to tillage on pesticide sorption. Ding et al (2002b) highlighted a stronger sorption of metolachlor by humin than by humic acids, and humin content was found to be higher under notillage systems (Stearman et al, 1989). For humin, which is a highly condensed form of soil organic matter, several studies showed that sorption was more variable and that sorption isotherms were less linear (Xing and Pignatello, 1997;Yuan and Xing, 1999).…”
Section: Organic Carbon Content Effectmentioning
confidence: 99%
“…For humin, which is a highly condensed form of soil organic matter, several studies showed that sorption was more variable and that sorption isotherms were less linear (Xing and Pignatello, 1997;Yuan and Xing, 1999). In contrast, Stearman et al (1989) observed a higher sorption of metribuzin and oxyfluorfen on fulvic and humic acids, which are abundant in conventional tillage, than on humin, which is abundant in conservation tillage. Dissolved organic carbon content is most often higher under conservation tillage and is mainly composed of small molecules, with a size similar to that of fulvic acids (Suba and Essington, 1999).…”
Section: Organic Carbon Content Effectmentioning
confidence: 99%
“…The pronounced reactivity of the OM is mainly related to its high specific surface area and presence of various functional groups such as carboxyl, hydroxyl and amine, and aliphatic and aromatic structures (STEVENSON, 1972;STEARMAN et al 1989;KUCKUK et al 1997). CHEFETZ et al (2004) observed greater adsorption of ametryn in sediment with 1.25 dag kg -1 of organic carbon in relation to the other with 1.63 dag kg -1.…”
Section: Organic Matter and Sorption Of Herbicides In The Soilmentioning
confidence: 98%
“…A MO apresenta acentuada capacidade de sorver herbicidas (Stevenson, 1972) e isto reduz a atividade biológica e a mobilidade dos compostos químicos aplicados ao solo (Lee & Farmer, 1989;Scheunert et al, 1992). A pronunciada reatividade da MO está relacionada principalmente com sua elevada área superficial específica e presença de vários grupos funcionais, como carboxilas, hidroxilas e aminas, e estruturas alifáticas e aromáticas (Stevenson, 1972;Stearman et al, 1989;Kuckuk et al, 1997).…”
Section: Introductionunclassified